One-Pot Glycosylation Strategy for Rapid Access of Oligosaccharides with Wide Range of Molecular Diversity - Sangwan, Rekha; Mandala, Pintu K. (Current Organic Chemistry, 2021)
In carbohydrate chemistry, the synthesis of complex saccharides with well-defined structures is the most formidable process as it is quite strenuous to isolate carbohydrates in acceptable purity and amounts from natural sources. Therefore, complex saccharides with well-defined structures are often most conveniently accessed through chemical syntheses. This review mainly focuses on the methodologies for one-pot glycosylation into the complex glycans from the non-reducing end to reducing end and vice versa, orthogonal, preactivation based, photochemical as well as hybrid one-pot glycosylation. The main goal of this review in the carbohydrate community was to rapidly synthesize biologically relevant glycans that can be implemented for research in carbohydrate-based vaccine development, diagnostics, as well as drug discovery.
Keywords: Glycosylation